Effect of phase change materials on the short-term thermal storage in the solar receiver of dish-micro gas turbine systems: A numerical analysis. (August 2021) - Bashir, Muhammad Anser; Daabo, Ahmed M.; Amber, Khuram Pervez; Khan, Muhammad Sajid; Arshad, Adeel; Elahi, Hassan
Highlights: Solar receiver with short-term thermal storage for Dish-Micro Gas Turbine system. Effect of suitable PCMs on the output parameters of PCM integrated solar receiver. Detailed numerical analysis using CFD methods. Steady state parametric analysis for the effect of important parameters of PCM. Detailed transient analysis for thermal storage behavior of the solar receiver. Abstract: The solar dish-micro gas turbine system is a new alternative to the existing technologies for small-scale power production (<100 kW) in rural off-grid areas. In these solar-only systems, the short-term thermal energy storage in the solar receiver reduces the effect of natural fluctuations of the solar flux and ensures the stable working fluid (WF) temperature to the gas turbine. It improves the system performance and stability of the small gas turbine. In this context, a concept of Phase Change Material (PCM) integrated solar receiver was presented by authors in previous studies, where the receiver was filled with high-temperature PCM and WF (air) tubes were immersed in it. The PCM stores heat during charging phase and releases heat during the solar breakdown. The selection of PCMs for this receiver is a challenging task due to the high operating temperature ( T m  > 1000 K). This study deals with the analysis of the impact of main parameters of the PCM on the performance of the solar receiver and detailed thermal analysis of the component using selected suitable PCMs. The 3D numerical analysis has been performed using Ansys Fluent R2. Moreover, the optical analysis has been carried out by ray tracing using SolTrace. The results of Soltrace are input to the Ansys Fluent and solar radiations are made to impinged on the cavity of the solar receiver. Steady-state parametric analysis has been performed considering the effect of latent heat of fusion, thermal conductivity, and the specific heat of the PCM on the outlet parameters of the receiver. The results showed a significant effect of these parameters on the heat storage of the solar receiver and the solidification/melting rate of PCM. The latent heat has major effect on the thermal storage in the PCM while thermal conductivity has high impact on the solidification/melting rate of the PCM. The transient simulations have been performed for the detailed melting/solidification behavior of the receiver using four metallic PCMs including MgSi, AlSb, NiSi, and Mg2 Si. AlSb is characterized with comparatively lower latent heat and high thermal conductivity and showed quick solidification in discharging phase. Mg2 Si has high melting temperature and a low thermal conductivity as compared to the other selected PCMs and thus has a comparatively slow solidification rate than AlSb and MgSi. The results show a good behavior of the component short term (15–20 min) thermal energy storage and stabilization of WF (air) temperature above 1000 K during this period.